2022
DOI: 10.1101/2022.03.06.483110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Downregulation of the secreted protein with an altered thrombospondin repeat (SPATR) impacts the infectivity of malaria sporozoites

Abstract: The identification of surface proteins of the sporozoite stage of malaria parasites important for sporozoite infectivity could aid in the improvement of the efficacy of vaccines targeting pre-erythrocytic stages. Thus, we set out to disclose the role of the secreted protein with an altered thrombospondin repeat (SPATR), which is highly expressed in sporozoites. Previous studies showed an essential function in blood stages, while no role was detected in sporozoites despite high expression. To achieve downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 80 publications
5
7
0
Order By: Relevance
“…Like CLAMP, SPATR is conserved in Apicomplexa and is essential in asexual blood stages of the parasite life cycle. Interestingly, a recent study based on conditional knockdown in P. berghei showed that sporozoites lacking SPATR have impaired motility, strongly reduced capacity to invade salivary glands and decreased infectivity to mice (Costa et al, 2022), a phenotype that is similar to the one we observed with CLAMP-deficient parasites. Costa et al excluded a role of SPATR in TRAP secretion, based on the detection of TRAP at the surface of mutant sporozoites by immunofluorescence (Costa et al, 2022).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Like CLAMP, SPATR is conserved in Apicomplexa and is essential in asexual blood stages of the parasite life cycle. Interestingly, a recent study based on conditional knockdown in P. berghei showed that sporozoites lacking SPATR have impaired motility, strongly reduced capacity to invade salivary glands and decreased infectivity to mice (Costa et al, 2022), a phenotype that is similar to the one we observed with CLAMP-deficient parasites. Costa et al excluded a role of SPATR in TRAP secretion, based on the detection of TRAP at the surface of mutant sporozoites by immunofluorescence (Costa et al, 2022).…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, a recent study based on conditional knockdown in P. berghei showed that sporozoites lacking SPATR have impaired motility, strongly reduced capacity to invade salivary glands and decreased infectivity to mice (Costa et al, 2022), a phenotype that is similar to the one we observed with CLAMP-deficient parasites. Costa et al excluded a role of SPATR in TRAP secretion, based on the detection of TRAP at the surface of mutant sporozoites by immunofluorescence (Costa et al, 2022). In our hands, surface staining of TRAP did not show any overt difference between untreated and rapamycin-treated parasites, irrespective of stimulation of microneme secretion (S3 Fig) . It is possible however that surface immunostaining may not capture the entire dynamics of TRAP secretion and shedding.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The latter corroborates prior work, which found that inhibitory antibodies can block P. falciparum invasion of blood cells (Chattopadhyay et al , 2003). In P. berghei, Pb SPATR is required for blood stages and is likely required in sporozoites, suggesting the CLAMP complex is important for host cell invasion in multiple stages of the parasitic life cycle (Gupta et al , 2020; Costa et al , 2022). Though we were unable to make a conditional knockdown strain for Pf CLIP, the PlasmoGEM project finds that the CLIP homolog in P. berghei is also essential during blood stages (Bushell et al , 2017).…”
Section: Discussionmentioning
confidence: 99%